Lesch-Nyhan Syndrome: Evaluation of a Modified Bite Device to Prevent Bite Injuries - Gaetano Ierardo; Valeria Luzzi; Gian Luca Sfasciotti; Antonella Polimeni; Maurizio Bossù (Applied Sciences, 2020)
Lesch-Nyhan syndrome (LNS) is a serious form of hypoxanthine-guanine phosphoribosyltransferase (HPRT) deficiency, a hereditary purine metabolism disorder. The prevalence reported in the literature is 1/380,000 to 235,000 births. Males are affected and females are heterozygous carriers. LNS patients present a combination of hypotonia, spasticity, and neurological and behavioral disorders. They also show an obsessive-compulsive self-injurious behavior with bites and injuries to the lips, tongue, cheeks and fingers. The literature offers little scientific contribution related to the management of this problem. The authors describe their experience with a 4-year-old LNS patient and present a viable solution to control and avoid bite injuries, namely a specifically modified bite. The patient was treated at the Pediatric Dentistry Department of “Sapienza” University of Rome with a modified bite with the internal surface, in contact with the teeth, realized in 2-mm-thick soft silicone, and the exterior part consisting of a transparent resin shell with front and rear shields to separate lips and cheeks from the dental arches. At a 12-month follow-up visit, compliance was excellent: the child wore the device with regularity and without discomfort, even during soft-food feeding. No intraoral bite injuries were found, with a general improvement of the young patient’s quality of life.